Kesadaran Mahasiswa UIN Maulana Malik Ibrahim Malang Terhadap Kasus Gratifikasi dalam Organisasi Kampus - jannah, miftachul (Maliki Interdisciplinary Journal, 2025)
Gratuity has become a critical and widespread issue in various sectors of life, including in the world of education. Campus is one of the places where gratuity practices run without being realized and even considered commonplace. This shows how important awareness of anti-gratuity culture must be instilled in students. For this reason, this research seeks to reveal the practice of gratuity in student organizations, as well as to find out the extent to which students understand the concept of gratuity related to corruption. The method used is a skinative research method with a case study approach, which is an approach carried out in an intensive, detailed and in-depth manner on a matter under study in the form of programs, events, activities and others to obtain in-depth knowledge or information. Data collection is done by conducting interviews through a questionnaire form. Based on the research results obtained, it shows that the majority of students are recipients of gratuities and few give them.A total of 68.8 respondents agreed that the gratuity practices exemplified in the illustration should not be normal and that there should be immediate and serious action taken, both from campus policy and all organizations on campus. While graft in student organizations may not be sanctioned immediately, it is important to be aware of its long-term impact. Student awareness and concern, supported by the active role of student organizations, can be key in creating a clean and gratification-free culture on campus and in the future.